Fish-dominated nekton assemblage structure and spatial-temporal variation in the intertidal zone of Bone Bay, South Sulawesi, Indonesia - ANDI MUHAMMAD REZA; MUSBIR MUSBIR; NAJAMUDDIN NAJAMUDDIN; FIJWAL PATANGNGARI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Reza AM, Musbir, Najamuddin, Patangngari F. 2026. Fish-dominated nekton assemblage structure and spatial-temporal variation in the intertidal zone of Bone Bay, South Sulawesi, Indonesia. Biodiversitas 27 (7): d270716. https://doi.org/10.13057/biodiv/d270716. The intertidal zone of Bone Bay, South Sulawesi, Indonesia, is characterized by fish-dominated nekton assemblages and traditional sero fisheries. However, there is a paucity of quantitative data on variation in gear-standardized assemblages. This study investigated the composition, diversity, and spatial-temporal structure of nekton assemblages captured using stationary sero traps at six intertidal stations from July to November 2025. A total of 7,448 individuals, representing 49 taxon records, were analyzed. Due to variations in leader-net/penaju length among stations, taxon abundance was standardized as catch per unit effort (CPUE; individuals m-1 trip-1) prior to multivariate analysis. The CPUE-based community matrix underwent square-root transformation and was analyzed using Bray-Curtis dissimilarity, NMDS, PERMANOVA, ANOSIM, PERMDISP, pairwise PERMANOVA, and SIMPER. NMDS yielded a low stress value of 0.132. PERMANOVA revealed significant effects of station and month, with station accounting for 44.47% of assemblage variation (F: 15.484, p<0.001) and month accounting for 26.82% (F: 11.673, p<0.001). Station-level PERMDISP was not significant, whereas monthly dispersion was significant, suggesting that temporal effects should be interpreted with caution. SIMPER analysis indicated that the most pronounced station contrasts were driven by both fishes and mobile crustaceans. Oceanographic variables were analyzed separately and served as environmental context rather than direct causal habitat drivers. These findings demonstrate significant station-level assemblage differentiation in gear-standardized intertidal sero catches, with additional short-term monthly variation.